2011
DOI: 10.1590/s0036-46652011000200005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of glycoprotein B genotypes and load of CMV infecting blood leukocytes on prognosis of AIDS patients

Abstract: SUMMARYBackground: Cytomegalovirus (CMV) remains an important pathogen to immunocompromised patients even in the era of HAART. The present study aimed at evaluating the influence of CMV viral load and its gB genotypes on AIDS patients' outcome. Methods: Blood samples of 101 AIDS patients were collected and tested for HIV load, CD4 -cell count and opportunistic pathogens, including CMV. Semi nested PCRs were run to detect CMV genome and in the positive samples, gB genotyping and CMV load were established using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…Among viral factors, genetic variability has been analyzed in order to determine the possible association between viral genetic features and infection outcome; several genes have been targeted for evaluation including those encoding for gB, glycoprotein N, glycoprotein O, and the UL144 gene, among others [6,11,12,13,14]. The gB gene has been studied in different risk groups, including both solid organ and hemopoietic transplant patients [5,15,16,17,18,19,20,21,22,23,24,25,26,27], HIV-infected patients [4,6,15,16,28,29,30,31,32,33], infants with congenital infection [3] and healthy subjects [34]. So far, studies directed towards assessing the impact of genotype features on disease have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among viral factors, genetic variability has been analyzed in order to determine the possible association between viral genetic features and infection outcome; several genes have been targeted for evaluation including those encoding for gB, glycoprotein N, glycoprotein O, and the UL144 gene, among others [6,11,12,13,14]. The gB gene has been studied in different risk groups, including both solid organ and hemopoietic transplant patients [5,15,16,17,18,19,20,21,22,23,24,25,26,27], HIV-infected patients [4,6,15,16,28,29,30,31,32,33], infants with congenital infection [3] and healthy subjects [34]. So far, studies directed towards assessing the impact of genotype features on disease have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies directed towards assessing the impact of genotype features on disease have yielded conflicting results. Nevertheless, it appears that in certain circumstances strain type may have a role in the occurrence of CMV disease; for instance, most studies in HIV-positive patients report gB2 as the most common genotype [4,6,15,16,28,29,30,31,32,33], while in transplant patients gB1 is the predominant genotype [5,15,16,17,18,19,20,21,22,23,24,25,26,27]. Also, the interpretation of these results is affected by the frequent detection of coinfections with two or more CMV strains in immunosuppressed patients [22,33].…”
Section: Discussionmentioning
confidence: 99%
“…According to the sequence variation of UL55 gene that encodes gB, there are four major gB genotypes(gB1, gB2, gB3, gB4) [1013]. In addition, three nonprototypic genotypes (gB5, gB6, gB7) have been identified [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, three nonprototypic genotypes (gB5, gB6, gB7) have been identified [14] [15]. Previous studies showed that gB2 is the predominant gB type in AIDS patients [1113, 16, 17]. However, the association of gB genotypes and disease progression is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that presence of gB2 genotype could be a predictor of patient's poor prognosis. [31] Roubalová et al (2009) had looked for the prevalence of CMV gB genotypes in various risk groups and gB2 (55%) was most dominantly seen in HIV patients. [32] In our study though gB1 genotype of CMV was predominant, we could not find any significant association of a particular genotype with HIV infection.…”
Section: Discussionmentioning
confidence: 99%